Vaginal Leiomyoma with Degenerative Changes - Mishra , Vineet; Solanki , Smit Bharat (Novel Research Aspects in Medicine and Medical Science Vol. 9, 2023)
Leiomyomas are common benign tumors in the uterus. They are rarely seen in the vaginal wall leading to pressure symptoms on urinary tract such as the vagina, utero-sacral ligament, inguinal canal, ovaries, and round ligament. Only a few number of vaginal origin fibroid cases have been reported in the literature. Vaginal leiomyomas are still a rare disorder, with just 300 cases known to exist. The anterior vaginal wall is where these vaginal fibroids most frequently develop, and they might show clinically in a number of ways. We report a case of vaginal lateral wall fibroid of 8 cm size and extending into paraurethral space. The vaginal mass was surgically excised and histopathology confirmed the diagnosis of leiomyoma with cartilaginous degeneration.